ANALYSIS OF INTERNATIONAL LEGAL STANDARDS FOR THE PROTECTION OF YOUTH LABOR ON THE EXAMPLE OF CONVENTIONS OF THE INTERNATIONAL LABOR ORGANIZATION - Murodullaev Dostonjon Nigmatullo ogli (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In this article, the powers of the International Labor Organization in the international legal regulation of labor, as well as the minimum age for employment in the International Labor Organization, the protection of youth labor, working hours and training, employment and employment assistance.